An Analysis Of Employee Work Discipline at PDAM Tirta Medal Sumedang - Muliani, Ciska Nisa; Puspasari, Rd. Dewi; Sukmayadi, Sukmayadi (SINTESA, 2025)
This research focuses on examining employee work discipline at PDAM Tirta Medal Sumedang, particularly in relation to punctuality and adherence to workplace rules. Utilizing a descriptive qualitative method, data were obtained through interviews and direct observations involving five selected informants. Findings reveal that the company has adopted measures such as an online attendance system, direct oversight, and a structured system of sanctions to strengthen employee discipline. While enforcement of rules regarding working hours and official attire has commenced, certain adjustments remain necessary, especially for employees working in the field. Although there are technical challenges like limited attendance system access for field staff and less-than-optimal application of rewards and penalties the overall employee discipline level is viewed as relatively good. This is evident in the company’s consistent efforts to uphold regulations and foster a responsible, disciplined work environment.